IMPLEMENTATION OF ENVIRONMENTAL LAW AND ENVIRONMENTAL PRESERVATION EFFORTS IN INDONESIA - Kriswandaru, Althea Serafim; Lubis, Arief Fahmi (PT. Altin Riset Publishing, 2024)
Objective study For the analysis of the implementation of environmental law and environmental conservation efforts in Indonesia, the methods used are method study qualitative and type study studies. References . Types of studies References used for digging deep understanding about a topic or phenomenon with analyzing literature And where are the relevant sources? in study This is related to the implementation of environmental laws and environmental conservation efforts in Indonesia. As for the data, it was obtained through the study and analysis of various references, like journals, scientific articles, and documents related to the topic being researched. Then, the researcher read an interesting thread and concluded from the results, findings, and study. Results study This leads to a conclusion. In the context of implementing environmental law and environmental conservation efforts in Indonesia, this research identifies a number of key aspects. Implementation of environmental law is faced with a number of challenges, including conflicts of interest, unequal access to the law, and differences in capacity at the regional government level. However, environmental conservation efforts in Indonesia also show positive initiatives, such as natural habitat conservation, reforestation programs, and renewable energy development. Technological and social innovations are key to increasing the effectiveness of conservation efforts.